2018
DOI: 10.1007/s00221-018-5340-1
|View full text |Cite
|
Sign up to set email alerts
|

More vection means more velocity storage activity: a factor in visually induced motion sickness?

Abstract: Full-field visual rotation around the vertical axis induces a sense of self-motion (vection), optokinetic nystagmus (OKN), and, eventually, also motion sickness (MS). If the lights are then suddenly switched off, optokinetic afternystagmus (OKAN) occurs. This is due to the discharge of the velocity storage mechanism (VSM), a central integrative network that has been suggested to be involved in motion sickness. We previously showed that visually induced motion sickness (VIMS) following optokinetic stimulation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 42 publications
3
24
1
Order By: Relevance
“…This hypothesis predicts that VIMS and cybersickness should: (1) never occur without vection; and (2) be more likely to occur, and more severe, during stronger vection. Consistent with the hypothesis, the findings of a number of VIMS and cybersickness studies appear to support these predictions (Hettinger et al, 1990;Flanagan et al, 2002;Smart et al, 2002;Bonato et al, 2004Bonato et al, , 2005Bonato et al, , 2008Diels et al, 2007;Palmisano et al, 2007;Nooij et al, 2017Nooij et al, , 2018Clifton and Palmisano, 2019;Risi and Palmisano, 2019). However, other studies have reported nonsignificant or negative relationships between vection and sickness Griffin, 2002, 2003;Lawson, 2005;Bonato et al, 2008;Ji et al, 2009;Chen et al, 2011;Golding et al, 2012;Keshavarz et al, 2014Keshavarz et al, , 2015Riecke and Jordan, 2015;Gavgani et al, 2017b;Palmisano et al, 2017Palmisano and Riecke, 2018;Kuiper et al, 2019;Teixeira and Palmisano, 2020).…”
Section: The Vection Conflict Hypothesismentioning
confidence: 80%
“…This hypothesis predicts that VIMS and cybersickness should: (1) never occur without vection; and (2) be more likely to occur, and more severe, during stronger vection. Consistent with the hypothesis, the findings of a number of VIMS and cybersickness studies appear to support these predictions (Hettinger et al, 1990;Flanagan et al, 2002;Smart et al, 2002;Bonato et al, 2004Bonato et al, , 2005Bonato et al, , 2008Diels et al, 2007;Palmisano et al, 2007;Nooij et al, 2017Nooij et al, , 2018Clifton and Palmisano, 2019;Risi and Palmisano, 2019). However, other studies have reported nonsignificant or negative relationships between vection and sickness Griffin, 2002, 2003;Lawson, 2005;Bonato et al, 2008;Ji et al, 2009;Chen et al, 2011;Golding et al, 2012;Keshavarz et al, 2014Keshavarz et al, , 2015Riecke and Jordan, 2015;Gavgani et al, 2017b;Palmisano et al, 2017Palmisano and Riecke, 2018;Kuiper et al, 2019;Teixeira and Palmisano, 2020).…”
Section: The Vection Conflict Hypothesismentioning
confidence: 80%
“…Full-field stimulation is also the most efficient way to induce circular vection (46). Additionally, the amount of circular vection is correlated with the duration of OKAN (56), which is directly related to the activation of velocity storage (47,57). Furthermore, OKAN can be induced by peripheral vision, while the central (foveal) vision is blocked or lessened (18,56).…”
Section: Discussionmentioning
confidence: 99%
“…The full-field OKN induces a sensation of body rotation in the direction opposite to stripes' motion (vection) that is indistinguishable from actual rotation in light with stripes stationary in space (46). It was recently demonstrated that amounts of vection and velocity storage are directly correlated (47). Thus, according to VOR readaptation hypotheses, when the ship is turning relative to the coastline, it induces horizontal OKN (yaw axis rotation), if the passenger is facing the ship's direction of motion.…”
Section: Introductionmentioning
confidence: 99%
“…This also implies a localizing value, as these patients will have impairments (or alterations) at the level of the cerebellum, where the activity of the velocity storage is supposedly controlled. Previous studies have shown prolonged horizontal OKAN after removal of the nodulus/uvula [37].…”
Section: Discussionmentioning
confidence: 84%